Nanoscale differences in the shape and size of X and Y chromosome-bearing bovine sperm heads assessed by atomic force microscopy. - José O Carvalho (Public Library of Science (PLoS), 2013)
Sperm dimensions and the question of whether X and Y chromosome-bearing sperm differ in size or shape has been of great interest, especially for the development of alternative methods to sort or classify sperm cells. The aim of the present study was to evaluate possible differences in the shape and size of the sperm head between X and Y chromosome-bearing sperm by atomic force microscopy (AFM). One ejaculate per bull (n = 4) was used. Each ejaculate was separated into four fractions: non-sexed (NS), sexed for X-sperm (SX), sexed for Y-sperm (SY) and a pooling of SX and SY samples (SXY). Using AFM, 400 sperm heads per group were measured. Twenty three structural features were assessed including one-, two- and three-dimensional parameters and shape descriptors. These measurements determine the micro- to nanoscale features of X- and Y-bearing chromosomes in sperm cells. No differences were observed for any individual variables between SX and SY groups. Next, a simultaneous evaluation of all features using statistical discriminant analysis was performed to determine if it was possible to distinguish to which group belong each individual cells. This analysis clearly showed, a distinct separation of NS, SXY, SX and SY groups. The recognition of this structural possibility to distinguish between X and Y sperm cell might improve the understanding of sperm cells biology. These results indicated that the associations of several structural measurements of the sperm cell head are promising candidates for development of a new method of sperm sexing.